The relationship between the strength of pain and the oral expressions among a sample of nerves patients in Lattakia. - charrouf, Ansab; halloum, Walaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to investigating the relationship between the strength of pain and expressions of pain among a sample of patients with inflammation of the nerves in Lattakia, and to find out the relationship between the strength of pain and sensory expressions of pain, and to find out the relationship between the strength of pain and Emotional expressions of pain. Participants were (40) patient from inflammation of the nerves, The measures of pain were EVA to strength of pain and Saint –Antoine scale to assess pain, and anxiety test as (state and trait), The results showed that there is correlation between the strength of pain and expressions of pain among the members of the sample as a whole, and there are correlation between the strength ofpain and sensory and emotional expressions of pain.